Decentralized cooperation between smart cities regarding renewable energies in the European Union: analysis of projects and actions - Abbondanzieri, Camila (2021)
Energy issues in the European Union have been present since the beginning of the integration process in the bloc. Motivated by the challenges of the 21st century and by the intensification of problems related to energy supply, the European Commission proposed changes that resulted in the profound transformation of energy systems through the proposal of the Energy Union in 2015. In this context, decentralized cooperation projects and actions between Smart Cities have been conducted. These implied associating sub-national dimensions with regional ones for the treatment of energy problems from an efficient and sustainable resource management perspective.